2017
DOI: 10.12659/msm.902343
|View full text |Cite
|
Sign up to set email alerts
|

Semivertical Incision: An Aesthetically and Electrophysiologically Effective Mini-Incision Technique for Carpal Tunnel Decompression

Abstract: BackgroundThe purpose of this study was to present the clinical results of our retrospective series of carpal tunnel release (CTR) operations. For these operations we used a unique type of incision, for the first time, for treatment of carpal tunnel syndrome (CTS) consisting of a 1-cm semi-vertical (SV) incision made into the wrist crease for macroscopic open CTR.Material/MethodsThis retrospective study included 114 patients (101 females and 13 males) with CTR who were operated upon in our neurosurgery clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Published studies have variably reported the affected age groups in their specific populations. For instance, Xu L et al from China reported a mean age of 41 years with a range of 27 to 55 years, whereas Keser N et al from Turkey reported the mean age to be 55 years, with a range of 35 to 83 years (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies have variably reported the affected age groups in their specific populations. For instance, Xu L et al from China reported a mean age of 41 years with a range of 27 to 55 years, whereas Keser N et al from Turkey reported the mean age to be 55 years, with a range of 35 to 83 years (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Several published papers are akin to this observation. The higher frequency among women has been attributed to a variety of factors such as the anatomically narrower carpal tunnel being prone to higher internal pressures causing median nerve compression (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative diagnosis based on one or more the following manifestations: hand pain, muscle weakness, hypoesthesia or paresthesia among median nerve [MN] distribution, atrophy of thenar muscles and positive signs [Tinel's, Phalen's, or Durkan's] [9] .…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The severity of CTS had graded according to The AAEM classification [10] . All electromyography studies had completed as described by Keser et al [9] .…”
Section: Electromyography [Emg]mentioning
confidence: 99%
“…Surgical treatment helps release the MN entrapped under the transverse carpal ligament within the carpal tunnel. Various surgical methods have been described in the literature for this purpose (2,8,10,13).…”
Section: Original Investigationmentioning
confidence: 99%